2016
DOI: 10.1002/bmc.3758
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of the chemical constituents in Mahuang‐Fuzi‐Xixin decoction based on high performance liquid chromatography combined with time‐of‐flight mass spectrometry and triple quadrupole mass spectrometers

Abstract: High-performance liquid chromatography coupled with time-of-flight mass spectrometry (HPLC-TOF/MS) and high-performance liquid chromatography-triple quadrupole mass spectrometry (HPLC-QQQ/MS/MS) were utilized to clarify the chemical constituents of Mahuang-Fuzi-Xixin Decoction. There are 52 compounds, including alkaloids, amino acids and organic acids were identified or tentatively characterized by their characteristic high resolution mass data by HPLC-QQQ/MS/MS. In the subsequent quantitative analysis, 10 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The limits of detection (LOD) and the limits of quantification (LOQ) were evaluated at a signal-to-noise ratio (S/N) of 3/1 and 10/1 respectively. The parameters of LOD and LOQ for each constituent in this experiment were from 0.05~164.95 ng.mL −1 and 0.05~824.74 ng.mL −1 (shown in Table 1 2930). …”
Section: Resultsmentioning
confidence: 99%
“…The limits of detection (LOD) and the limits of quantification (LOQ) were evaluated at a signal-to-noise ratio (S/N) of 3/1 and 10/1 respectively. The parameters of LOD and LOQ for each constituent in this experiment were from 0.05~164.95 ng.mL −1 and 0.05~824.74 ng.mL −1 (shown in Table 1 2930). …”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometric and chromatographic detection identified 52 compounds, including alkaloids, amino acids and organic acids. The main constituents are methyl ephedrine, aconine, songrine, fuziline, neoline, alatisamine, chasmanine, benzoylmesaconine, benzoylaconine, and benzoylhypaconine (Sun et al, 2016 ). Experiments showed that MFX decoction significantly depressed the expression of IL-6, MCP-1 and TNF-α, and markedly increased expression of IL-10 in serum, indicating the effect of reducing inflammation and increasing antioxidant activities (Tang et al, 2015 ; Rong et al, 2016 ).…”
Section: Tcm For Bradyarrhythmia Evidence and Mechanismsmentioning
confidence: 99%
“…The MS/MS device is well suited for quantitative determination of known compounds in the selected reaction monitoring mode . In addition, TOF mass analyzers (eg, QTOF/MS) providing high sensitivity and mass accuracy are suitable for the structural elucidation of unknown compounds, and are particularly useful for the analysis of HM …”
Section: Mass Spectrometry: the “Microscope” For Chemical Structuresmentioning
confidence: 99%